p16(INK4a) and p15(INK4b) gene promoter methylation in cervical cancer patients - JHA, ABHIMANYU KUMAR (D.A. Spandidos, 2012)
The aim of this study was to determine the methylation status of the p16(INK4a), p14(ARF) and p15(INK4b) genes and the subsequent effect of hypermethylation on the expression of these genes in cervical cancer patients. Methylation-specific PCR (MSP) was performed to analyse the methylation status of p16(INK4a), p14(ARF) and p15(INK4b) genes and was confirmed by sequencing. Reverse transcription PCR (RT-PCR) was carried out to determine changes in the expression of the genes due to hypermethylation. Hypermethylation of the p16(INK4a), p14(ARF) and p15(INK4b) gene promoters was observed in 36, 8.8 and 11.2%, respectively, of 125 cervical cancer samples from a north Indian population. Methylation of p16(INK4a) was significantly (P<0.001) associated with the cervical cancer cases. Significant association of p16(INK4a) hypermethylation with passive smoking and oral contraceptive use was also observed. Methylation of p15(INK4b) was also found to be significant (P<0.05). Our findings did not reveal any correlation between the promoter methylation of p16(INK4a), p14(ARF) and p15(INK4b) with factors, including age and human papillomavirus infection. mRNA expression was significantly reduced in patients with a methylated promoter (P<0.001) of p16(INK4a) compared to patients with an unmethylated promoter. In conclusion, this is the first study demonstrating significant hypermethylation of p15(INK4b) and p16(INK4a) genes among cervical cancer patients in a north Indian population, and a significant association of p16(INK4a) hypermethylation with passive smoking and oral contraceptive use.